Pergeseran Orientasi Nilai Kultural dan Keagamaan di Indonesia (Sebuah Esai dalam Rangka Mengenang Almarhum Prof. Koentjaraningrat) - Amri Marzali (Antropologi Indonesia, 2006)
This article is dedicated to the late Prof. Koentjaraningrat. It attempts to trace the history and the source of a concept and method used by Koentjaraningrat in a research and many of his speeches in the period of 1960-70s. The concept is called 'orientasi nilai-budaya'. The author finds that the concept was borrowed from the concept 'value orientation' used by Florence Kluckhohn and Fred Strodbeck, which was printed in their book, Variations in Value Orientation (1961). The concept 'value orientation' was originally stems from the concept 'value', which was once developed by Clyde Kluckhohn, the husband of Florence Kluckhohn, at Harvard University USA. This explanation, according to the author, is important for the student of anthropology in Indonesia. In the final of the article, the author attempts to apply the concept to the socio-cultural changes in contemporary Indonesia, particularly among the members of Islamic community. Key words: value orientation; value; socio-cultural changes.